SELF DOUBLE EMULSIFYING DRUG DELIVERY SYSTEM (SDEDDS): A REVIEW - Padole, Atul; Bodhankar, Mitali (Journal of Drug Delivery and Therapeutics, 2012)
Self emulsifying drug delivery systems (SEDDS) are well known for its potential to improve the aqueous solubility and oral absorption of lipophilic drugs. Self double-emulsifying drug delivery system (SDEDDS) are basically used for drugs having low solubility in water, but its potential application for the drugs defined as â€œhigh solubility low permeability classâ€ or a biopharmaceutical classification system [BCS] class III drug is appreciable, in which gastrointestinal permeation is the rate controlling step in the absorption process. The most important factor affecting the oral absorption of a drug, besides dissolution, is the permeability of the drug across the gastrointestinal lining. Improving permeability may, therefore, potentially improve the bioavailability of a drug. In this review we discuss the preparation, stability, formulation and characterization of SDEDDS. Â  Key Words: Multiple emulsion, self emulsifying, Protein peptide drug delivery, High soluble poorly permeable drugs.